Comparative assessment of skin reactivity to thimerosal- or phenol-preserved Imunoleish® antigen in dogs with suspected American Tegumentary Leishmaniasis in an endemic area of the state of Rio de Janeiro, Brazil - Raksa, Helen Caroline; Peres Lima dos Santos, Ginelza; de Oliveira Schubach, Armando; Kardec R. Galardo, Allan; T. B. Freitas, Ana Paula; Mouta Confort, Eliame; Sanavria, Argemiro; Borges Figueiredo, Fabiano (Acta Biológica Paranaense, 2022)
The leishmanin skin test (LST), which is an in vivo test that assesses the cellular immune responses to Leishmania-derived antigens, is an important tool in the laboratory diagnosis of American tegumentary leishmaniasis (ATL). This study aimed to compare the results obtained in LST employing the Imunoleish® antigen preserved with thimerosal (AgT) or phenol (AgP) and serological techniques to detect a possible infection caused by Leishmania (Viannia) braziliensis in dogs. The study included 172 dogs from an area endemic for ATL in the municipality of Paracambi, state of Rio de Janeiro, Brazil. The results obtained with Imunoleish® antigen preserved with thimerosal (AgT) or phenol (AgP) and serological tests were compared. Each dog received, intradermally, 0.1 mL of each antigen on the inner side of the right (AgT) and left (AgP) thighs. Five (2.7%) dogs presented ATL lesions. Of these, two were reactive to both formulations and three were reactive only to AgT. Among the 172 dogs, 68 (39.5%) were reactive only to AgT, 16 (9.3%) only to AgP, and 11 (6.4%) to both formulations. Twenty-one (12.2%) sera samples were reactive by immunofluorescent antibody test (IFAT) and 21 enzyme-linked immunosorbent assay (ELISA). However, in only two dogs out of the five which Leishmania was isolated from, serological tests were positive. The LST and serological tests could be a useful tool in the diagnosis of L. (V.) braziliensis infection in dogs. Standardization of the techniques and reagents used could allow comparative studies on sensitivity, specificity, and positive and negative predictive values in dogs from different regions. Keywords: American Tegumentary Leishmaniasis, Leishmanin skin test, Diagnosis, Dogs, Host